Pengaruh Kepemilikan Manajerial, Profitabilitas, Liability, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019 - Melati Lumbantoruan; Nina Purnasari; Yeslia Sarawati Hutabarat; Unjur Malo Madris Sinaga; Hot Rikardo Marpaung (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aimed to analyze and examine the effect of managerial ownership, profitability, Liability, and firm size on firm value in basic and chemical industrial sector companies listed on the Indonesia Stock Exchange in 2016-2019. The research method used is a quantitative method. The population in this study was 71 companies and the sample was 23, so the total data were 92 companies. Data analysis using SPSS 20 application, through T test, F test, and multiple linear analysis methods. The results showed, the results of the F test showed that the calculated F value > F table was 2.897 > 2.32, with a significance of 0.028 > 0.05. The results of the T test analysis are as follows, a) the managerial ownership variable has a T count < T table or 0.895 < 1.98973; b) the profitability variable has a value of T count < T table or -0.559 < 1.98973; c) variable Liability has a value of T count < T table or 3.198 > 1.98973; d) firm size variable has a value of T count < T table or 0.078 < 1.98973. In conclusion, partially the variables of Managerial Ownership, Profitability and Firm Size do not have a positive and insignificant effect on firm value, while the Liability variable has a positive and significant effect on firm value. Simultaneously the variables of Managerial Ownership, Profitability, Liability, and Company Size have a major influence on firm value. Keywords: Managerial Ownership, Liability, Firm Value, Profitability, Company Size